Postcard to Max Bredig, June 19, 1917 (1917)
Postcard sent to Max Albert Bredig (1902-1977) featuring a portrait of General Erich Ludendorff (1865-1937).
Keywords: Bredig, Max Albert, 1902-1977; Ludendorff, Erich, 1865-1937